RENAL DYSFUNCTION IN YOUNG MEN OF DRAFT MILITARY AGE, SUFFERING FROM ARTERIAL HYPERTENSION AND URIC METABOLISM DISTURBANCES - V. A. Lusov; Yu. M. Mashukova; E. M. Evsikov; N. V. Teplova; A. A. Oshnokova (Российский кардиологический журнал, 2009)
To clarify the specific features of renal dysfunction and their role in arterial hypertension (AH) progression, in 60 men of draft military age (16-26 years) and 79 parents, a complex clinical, laboratory and instrumental examination was performed. It included plasma uric acid and microalbuminuria measurement, dynamic and static scintigraphy, renal ultrasound tomography, renal artery Doppler ultrasound, echocardiography, and 24-hour blood pressure monitoring. The patients with AH, hyperuricemia, and nephropathy demonstrated microproteinuria, cylindruria, reduced tubular concentration ability, and disturbed renal secretion and excretion, typically bilateral. Individuals with hyperuricemic nephropathy more often had renal disease, diabetes mellitus, or obesity in family history, demonstrated higher levels of plasma creatinine and glucose, as well as higher prevalence of obesity and left ventricular hypertrophy. Hyperuricemic nephropathy should be considered as a separate form of secondary AH.